2022
DOI: 10.1038/s41598-022-10976-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute high-intensity exercise on myocardium metabolic profiles in rat and human study via metabolomics approach

Abstract: Acute high-intensity exercise can affect cardiac health by altering substance metabolism. However, few metabolomics-based studies provide data on the effect of exercise along with myocardial metabolism. Our study aimed to identify metabolic signatures in rat myocardium during acute high-intensity exercise and evaluate their diagnostic potential for sports injuries. We collected rat myocardium samples and subjects’ serum samples before and after acute high-intensity exercise for metabolite profiling to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Exercise is important in preventing cardiovascular disease, and moderate-intensity endurance training is especially beneficial in this regard. There is still some debate over whether acute high-intensity exercise (a short burst of vigorous exercise using a lot of energy) is harmful or beneficial for the heart; it certainly carries adverse risks in relation to dangerously high exercise intensity, whereby increased myocardial oxygen demand can result in myocardial ischemia and increased PPCP (Wu et al, 2022). This study showed that high-intensity physical activities per week were significantly related to reduced PPCP incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is important in preventing cardiovascular disease, and moderate-intensity endurance training is especially beneficial in this regard. There is still some debate over whether acute high-intensity exercise (a short burst of vigorous exercise using a lot of energy) is harmful or beneficial for the heart; it certainly carries adverse risks in relation to dangerously high exercise intensity, whereby increased myocardial oxygen demand can result in myocardial ischemia and increased PPCP (Wu et al, 2022). This study showed that high-intensity physical activities per week were significantly related to reduced PPCP incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Previous metabolomics studies showed that acute exercise was associated with high oxidative stress and increased phosphatidylcholine levels that might impair utilization of cardiac fatty acids and lead to inflammation-related metabolic disorders ( Paapstel et al, 2018 ; Wu et al, 2022 ). Yet, our results showed that long-term exercise could exert a favorable effect on cardiovascular system by reducing phosphatidylcholine concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…25,26,28,40,52,53 In 2022, 18 studies used a traditional non-targeted metabolomics assay. 18,24,30,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] Perhaps the most thought-provoking exercise metabolomics publication from 2022 came from the Long Lab at Stanford University and was published in Nature. This study identified an exercise-induced metabolite, namely N-lactoylphenylalanine (Lac-Phe), to be associated with reduced dietary intake.…”
Section: Metabolomicsmentioning
confidence: 99%
“…In 2022, 18 studies used a traditional non‐targeted metabolomics assay 18,24,30,83–97 . Perhaps the most thought‐provoking exercise metabolomics publication from 2022 came from the Long Lab at Stanford University and was published in Nature .…”
Section: Analytical Approaches For Ms‐based Investigations In Ses In ...mentioning
confidence: 99%